Super Encryption of the Hill Cipher Method and the AES Method for Security of Employee Salary Data - Sitepu, Ervina Br; Fauzi, Achmad; Rahmadani, Rahmadani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Data security is a security system that is needed to protect data in systems, networks and other digital components. In a unit or agency such as the South Binjai sub-district office, the management of employee salary data is done digitally, namely via a computer. However, in this increasingly sophisticated digital era, it can cause many irresponsible individuals to easily wiretapping the company's data so that it can be easily accessed by other parties, as well as employee salary data which contains a lot of data. important. In order to avoid unwanted things such as theft of personal data by irresponsible persons, a security system is needed that can maintain the confidentiality of data and secure data. Therefore, in this case, a security system is needed that can maintain the confidentiality of data and secure employee salary data. With that there are many algorithms that can be used in securing employee salary data. And the algorithm used is hill cipher and AES algorithm. The hill cipher algorithm is an encryption-decryption algorithm that uses a transformation matrix. The AES algorithm is a symmetric block ciphertext that can encrypt and decrypt information. The use of these two algorithms can further strengthen the security of employee salary data. From the results of the trials carried out, the sample data used containing employee salary data was successfully secured with both hill cipher and AES algorithms.